Ambient loop district heating and cooling networks with integrated mobility, power and interseasonal storage. (May 2022) - Revesz, Akos; Jones, Phil; Dunham, Chris; Riddle, Anthony; Gatensby, Norman; Maidment, Graeme
This paper describes a heat pump investigation for GreenSCIES (GS), a fifth Generation district heating and cooling (5DHC) network in Islington, London. The paper describes the GreenSCIES concept integrating Mobility, Power and Heat into a Smart Local Energy System (SLES). At the heart of the system is an ultra-low temperature ambient loop network, which permits bi-directional flow within the pipes to allow energy exchange between heating and cooling customers at different times and in different locations, depending on where demand is at any given time. An existing data centre provides the primary source of waste heat for the scheme. Heat pumps in distributed energy centres are utilised to amplify the temperature of the ambient loop to deliver heat in connected buildings. The energy centres integrate heat pumps with building-mounted solar photovoltaic (PV) systems and electric vehicle (EV) charging points. The paper provides an overview of the integrated SLES concept, focussing on the heat pump selection and the short and long-term thermal storage options designed for the scheme. The results show that even the smaller constructible 'New River' scheme will save 5, 000 tons of CO2 e annually. This will tend to 100% as the grid decarbonise further. Therefore, the GS SLES concept applied to urban areas could deliver significant carbon emission savings in the UK and elsewhere. Practical application: Project GreenSCIES, is a detailed design study to develop a Smart, Local Energy System (SLES) for a large community in the London Borough of Islington. Our consortium have developed an innovative SLES concept, centred around a fifth generation district heating and cooling network. The GS ambient loop systems have negligible losses and much greater efficiencies than traditional district heat networks. As recognised by the UK Government's Heat and Buildings Strategy, ambient loop systems should be considered where large-scale neighbourhood regeneration occurs. The proposed SLES concept applied to wider urban areas could deliver significant carbon emission savings in the UK.